Strategi Komunikasi Akun Instagram @apdcindonesia Dalam Meningkatkan Kesadaran Pengikutnya Mengenai Kesehatan Mental - Ndolu, Michell Audry (Brand Communication, 2023)
The World Health Organization reports that every year there are more than 700,000 people who die due to suicide. In this regard, individual mental health is one of the factors that is usually closely associated with. To decrease the suicide rate of the public, many long-term management programs are needed, for example counseling and education. APDC Indonesia is a professional consulting agency in the field of psychology that actively shares education about mental health on Instagram. This study aims to analyze the communication strategy that is implemented on Instagram account @apdcindonesia to increase the awareness of its followers about mental health. Through the content shared, they hope to increase followers’ awareness about mental health so they will be the best version of themselves. This is a descriptive qualitative research using in-depth interview as the data collection technique. The results of this study are analyzed using the 4 C’s for a social operation system, which are important elements in operating social media which include context, communication, collaboration, and connection. APDC Indonesia can be considered successful in carrying out its communication strategy on Instagram as seen from the interactions that occur with the audience and their enthusiasm in participating in the programs and services provided by APDC Indonesia. However, APDC Indonesia still needs to increase the intensity of responding to the comments so the connection element can be entwined deeper with their followers.